Analysis of the Influence of Brand Image, Product Quality and Perception of EduBP Product Price on Customer Loyalty with Customer Satisfaction Mediation Variables - Fachrodji, Achmad; Wulandari, Ririn; Chabib, Lutfi (Green Publisher Indonesia, 2025)
Indonesia’s literacy crisis, evidenced by its low PISA rankings (score: 371; rank: 74/79) and the collapse of major bookstores (e.g., Gunung Agung, Kinokuniya), underscores the urgency for innovative solutions like Balai Pustaka’s EduBP, a digital literacy platform. Despite its potential, EduBP’s sales remain low (16.5% of revenue), necessitating research into consumer behavior to enhance adoption. This study investigates how brand image, product quality, and price perception influence customer loyalty, mediated by customer satisfaction, in the context of EduBP’s digital platform. Using purposive sampling, 125 EduBP users were surveyed via Likert-scale questionnaires. Data were analyzed using SEM-PLS, with validity (KMO > 0.5; loading factor > 0.4) and reliability (Cronbach’s Alpha > 0.6) tests ensuring robustness. Brand image significantly drives satisfaction (β = 0.476, *p* = 0.001) and loyalty (β = 0.295, *p* = 0.004), while product quality shows no effect. Price perception indirectly affects loyalty (β = 0.703, *p* = 0.000) but not satisfaction. Customer satisfaction strongly mediates loyalty (β = 0.703, *p* = 0.000). Balai Pustaka must prioritize brand reputation and CRM strategies (e.g., after-sales service) over quality enhancements. Future research should explore market segmentation and technology acceptance factors (TAM) to refine digital literacy strategies. This study contributes to the nascent literature on digital product loyalty in emerging markets.